(untitled) (Ustozlar uchun, 2025)
The development of locally manufactured biopharmaceuticals in the Republic of Uzbekistan requires comprehensive preclinical evaluation of their safety, pharmacological activity, and therapeutic equivalence to internationally recognized reference products. Granulocyte colony‑stimulating factor (G‑CSF) preparations play a pivotal role in the prevention and treatment of neutropenia associated with cytotoxic chemotherapy, radiation exposure, and various immunopathological conditions.